Complete remission with ibrutinib after allogeneic stem cell transplant for central nervous system relapse of mantle cell lymphoma: A case report and literature review. Issue 10 (3rd September 2019) - Rich, Jessica D.; Clark, Stephen M.; Fedoriw, Yuri; Jewells, Valerie; Wood, William; Dittus, Christopher
Abstract: Central nervous system (CNS)‐relapsed mantle cell lymphoma (MCL) is a rare, aggressive non‐Hodgkin lymphoma without a standard treatment. Ibrutinib has shown promising results for inducing remission in other non‐Hodgkin lymphomas and may be considered as successful treatment for CNS‐relapsed MCL in the future as well. Abstract : Central nervous system (CNS)‐relapsed mantle cell lymphoma (MCL) is a rare, aggressive non‐Hodgkin lymphoma without a standard treatment. Ibrutinib has shown promising results for inducing remission in other non‐Hodgkin lymphomas and may be considered as successful treatment for CNS‐relapsed MCL in the future as well.